KEBAKTIAN PEMUDA SE-SUMATERA BAGIAN SELATAN (KPS) ke-27 TEMA : STRONG GENERATION BAGI PEMUDA-PEMUDI DI SUMATERA BAGIAN SELATAN (SUMSEL) - Butar-Butar, Marlon; Tembay, Aris Elisa; Manafe, Yanjumseby Yeverson Manafe; Kusradi, Sri Wahyuni; Siagian, Rustam; Kaseke, Fanny Yapi Markus; Lalaziduhu Harefa, Febriaman; Obet Nego (PkM: Pistotites, 2021)
Abstract The Southern Sumatran Youth Service (KPS) is one of the regular programs of the services of MD YPPII Batu, SumBagSel and Ebenhaezer Theological College. This activity is carried out every year, with the aim that the younger generation understands themselves, their role for God and their respective churches. The Southern Sumatran Youth Service was socialized and aimed at young people aged 16 and over. Youth and women are the next generation of the nation and the church. Therefore, the Community Service Team carried out services at the YPPII Batu Regional Assembly and the Tanjung Enim Theological High School of Ebenhaezer by carrying out the Southern Sumatran Youth Service (KPS). This devotional program is routinely carried out every year, the theme this year is Strong Generation, the purpose of this theme is to invite young people to become a strong or resilient generation in facing today's challenges, and so that young people can meet, know and believe and accept Jesus Christ as a personal savior, and become an opportunity to share experiences as children of God in social life. Abstrak Kebaktian Pemuda Se-Sumatera Bagian Selatan (KPS) adalah Salah satu program tetap dari pelayanan MD YPPII Batu SumBagSel dan Sekolah Tinggi Theologia Ebenhaezer. Kegiatan ini dilaksanakan setiap tahun, dengan tujuan agar generasi muda memahami dirinya, perannya bagi Tuhan dan gereja masing-masing. Kebaktian Pemuda Se-Sumatera Bagian Selatan disosialisasikan dan ditujukan kepada pemuda-pemudi dengan usia 16 keatas. Pemuda dan pemudi adalah generasi penerus bangsa dan gereja. Karena itu, Tim Pengabdian Masyarakat melaksanakan pengabdian di Majelis Daerah YPPII Batu dan Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim dengan melaksanakan Kebaktian pemuda Se-Sumatera Bagian Selatan (KPS). Program kebaktian ini rutin dilaksanakan setiap tahunnya, tema yang diusung tahun ini adalah Strong Generation (generasi kuat), tujuan dari tema ini adalah mengajak para anak muda untuk menjadi generasi yang kuat atau tangguh dalam menghadapi tantangan zaman sekarang, dan agar para pemuda dapat bertemu, mengenal dan percaya serta menerima Yesus Kristus sebagai juruslamat pribadi, dan menjadi kesempatan untuk saling membagi pengalaman sebagai anak-anak Tuhan dalam hidup bermasyarakat.